Biofilm Engineering Approaches for Improving the Performance of Microbial Fuel Cells and Bioelectrochemical Systems - Angelaalincy, Maria Joseph; Navanietha Krishnaraj, Rathinam; Shakambari, Ganeshan; Ashokkumar, Balasubramaniem; Kathiresan, Shanmugam; Varalakshmi, Perumal (Frontiers in Energy Research, 2018)
Microbial fuel cells (MFCs) are emerging as a promising future technology for a wide range of applications such as bioremediation, desalination, production of biofuels/value-added products in addition to sustainable electricity generation. Electroactive (EA) biofilms are the key players in any bioelectrochemical systems including MFCs. They are involved in the catalyzing oxidation/reduction reactions as well as mediating the electron transfer at electrode-electrolyte interfaces. Low power output of the MFCs remains a major limitation in MFCs and biofilm engineering is an ideal option for improving the rates of microbial electrocatalysis. Herein, we critically address the biofilm formation mechanisms in electroactive microorganisms, strategies for improving the biofilm formation leading to improved electrocatalytic rates for applications in bioelectrochemical systems.